GREEN SYNTHESIS OF GOLD NANOPARTICLES USING MUSA BALBISIANA BRACT EXTRACT - BORNALI BAISHYA,; MOHAN CHANDRA KALITA, (International Journal of Pharma and Bio Sciences, 2013)
Present study explores the biosynthesis and characterization of gold nanoparticles using the ethanolic bract extract of banana (Musa balbisiana) flower. On treatment of aqueous solutions of Chloroauric acid with M. balbisiana leaf extract, stable gold nanoparticles were rapidly formed in room temperature within 1 hour. The gold nanoparticles were characterized by UV-visible spectroscopy, Transmission Electron Microscopy (TEM), X- ray Diffraction studies (XRD) and Fourier Transform Infra-red Spectroscopy (FTIR). Surface Plasmon Resonance Spectra for gold nanoparticles are obtained at 530nm with pink-red color. Further FTIR analysis was also done to identify the functional groups in gold nanoparticles.